The Government's Policy Support for the Resistance and Local Wisdom of Fishermen on the North Coast of Java - Adzkiyak, Adzkiyak; Sudahri (POLITICO, 2024)
This research examines The Government's Policy Support toward the resistance and local wisdom of fishermen on the North Coast of Java. The phenomenon of fishermen's attitudes on the North Coast of Java in facing structural injustice uses an ethnographic approach. The research was conducted over six months in three different locations to explore four key attitudes summarized in local concepts: received (accept with resignation) the policy, gave up (give in) to the impact of the policy, switch (avoid/shift) from the impact of the policy, and angry (against) policies that are not pro-fishermen. Through participatory observation and in-depth interviews with 45 fishermen. The results of the study indicate that the impartial of government policies towards the resistance and local wisdom of fishermen on the North Coast of Java gives rise to injustices faced by fishermen originating from three main factors: impartial government policies, competition with industrial vessels, and exploitative marketing systems. The pattern of fishermen's attitudes moves dynamically from accept to angry, influenced by socio-economic conditions, education levels, and collective experiences. This study contributes to the understanding of everyday resistance in the context of Indonesian coastal communities and provides recommendations for fisheries policy reforms that are more equitable and pro-small-scale fishermen.